The Convergence of Customary Law and Islamic Law: Adoption and Inheritance Rights of Adopted Children in Batak Angkola - Nasution, Ulfa Ramadhani (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2024)
This article explores the interplay between customary and Islamic law in the Batak Angkola community, with a focus on child adoption and inheritance distribution. Using Alan Watson’s legal transplantation theory, this study examines how accessibility, habit, and mode (the latest trend) influence the adaptation of these legal practices. Findings reveal that the traditional adoption ceremony, which recognizes adopted children as biological heirs and involves significant costs and time, is becoming obsolete and is gradually abandoned. Consequently, adopted children are no longer regarded as biological heirs, leading to the logical application of compulsory bequest (wasiat wajibah) as a mechanism to grant inheritance rights limited to one-third of the estate. The frequent application of this practice suggests its potential evolution into a living customary law. The adaptation of wasiat wajibah reflects the alignment of customary law with Islamic legal principles, which emphasize justice and procedural ease. This shift underscores society’s preference for efficiency and practicality while preserving adherence to tradition. Thus, the continuous interaction between customary and Islamic legal frameworks fosters legal pluralism, enhances responsiveness to social changes, upholds maṣlaḥah (public welfare), and facilitates the evolution of legal traditions in response to contemporary societal needs.